The Influence of HR Competence and Intellectual Capital on the Performance of MSMEs in Sasirangan Craftsmen - Sampurnawati, S.; Agustina, Titien (Yayasan Ahmar Cendekia Indonesia, 2021)
This study aims to (1) describe the competence of Human Resources (HR), intellectual capital and the performance of Micro, Small and Medium Enterprises (MSMEs) engaged in the production of Sasirangan, a typical cloth of South Kalimantan (2) Analyze the influence of the level of competence of Human Resources ( HR) and intellectual capital on the performance of Sasirangan MSMEs. (3) Analyzing the competence of Human Resources (HR) and intellectual capital have a dominant effect on the performance of Sasirangan SMEs. Associative research method on 40 respondents taken by total sampling method. The data analysis technique used multiple linear regression. The results showed that the competence of Human Resources (HR) and intellectual capital had a positive and significant effect on the performance of MSMEs. Between these two variables, intellectual capital has a more dominant influence on Sasirangan MSMEs.